Pleiotropic effect of sigE over‐expression on cell morphology, photosynthesis and hydrogen production in Synechocystis sp. PCC 6803. (19th September 2013) - Osanai, Takashi; Kuwahara, Ayuko; Iijima, Hiroko; Toyooka, Kiminori; Sato, Mayuko; Tanaka, Kan; Ikeuchi, Masahiko; Saito, Kazuki; Hirai, Masami Yokota
Summary Over‐expression of sigE, a gene encoding an RNA polymerase sigma factor in the unicellular cyanobacterium Synechocystis sp. PCC 6803, is known to activate sugar catabolism and bioplastic production. In this study, we investigated the effects of sigE over‐expression on cell morphology, photosynthesis and hydrogen production in this cyanobacterium. Transmission electron and scanning probe microscopic analyses revealed that sigE over‐expression increased the cell size, possibly as a result of aberrant cell division. Over‐expression of sigE reduced respiration and photosynthesis activities via changes in gene expression and chlorophyll fluorescence. Hydrogen production under micro‐oxic conditions is enhanced in sigE over‐expressing cells. Despite these pleiotropic phenotypes, the sigE over‐expressing strain showed normal cell viability under both nitrogen‐replete and nitrogen‐depleted conditions. These results provide insights into the inter‐relationship among metabolism, cell morphology, photosynthesis and hydrogen production in this unicellular cyanobacterium.